Effect of Silica Fume as Cementitious Material and Waste Glass as Fine Aggregate Replacement Constituent on Selected Properties of Concrete - Keerio, M.A. (Springer Science and Business Media B.V., 2022)
Carbon dioxide emissions from cement production have a significant impact on the environment. The huge energy consumption in the cement production process is also a problem. Pakistan is responding to a severe energy crisis. The price of cement is growing day by day. In addition, the use of waste for the disposal and recovery of natural concrete components can cause environmental degradation. Using waste not only reduces cement production, thereby lowering energy consumption, but also helps to protect the atmosphere. The aim of this research is to study the properties of concrete using silica fume as a partial replacement of cement and glass waste instead of fine aggregate. This research includes the study of workability, water absorption, compressive strength and split tensile strength. In this experimental study, 5, 10 and 15 by weight of cement were replaced with silica fume, and fine aggregates were replaced with 10, 20, 30 and 40 by waste glass powder. A total of 20 mixtures in which one control mix, three mixes with addition of silica fume, four mixes with incorporating of glass powder and twelve mixtures with combined use glass powder and silica fume were prepared with 1:2:4 mix ratio at 0.5 water-binder ratios. According to the study parameters, replacing 10 cement with SF and 30 fine aggregate with glass powder is the best choice for optimum strength. Moreover, the utilization of glass powder and silica fume together significantly reduces the workability and water absorption of the composite concrete mixture. Â© 2020, Springer Nature B.V.